Telugu letters dataset and parallel deep convolutional neural network with a SGD optimizer model for TCR - Phaniram, Josyula Siva; Reddy, Mukkamalla Babu (Institute of Advanced Engineering and Science, 2024)
Because of the rapid growth in technology breakthroughs, including multimedia and cell phones, Telugu character recognition (TCR) has recently become a popular study area. It is still necessary to construct automated and intelligent online TCR models, even if many studies have focused on offline TCR models. The Telugu character dataset construction and validation using an Inception and ResNet-based model are presented. The collection of 645 letters in the dataset includes 18 Achus, 38 Hallus, 35 Othulu, 34×16 Guninthamulu, and 10 Ankelu. The proposed technique aims to efficiently recognize and identify distinctive Telugu characters online. This model's main pre-processing steps to achieve its goals include normalization, smoothing, and interpolation. Improved recognition performance can be attained by using stochastic gradient descent (SGD) to optimize the model's hyperparameters.